Functional identity explains carbon sequestration in a 77‐year‐old experimental tropical plantation. Issue 10 (28th October 2015) - Bauters, Marijn; Ampoorter, Evy; Huygens, Dries; Kearsley, Elizabeth; De Haulleville, Thales; Sellan, Giacomo; Verbeeck, Hans; Boeckx, Pascal; Verheyen, Kris
Abstract : Planting forests is an important practice for climate change mitigation, especially in the tropics where the carbon (C) sequestration potential is high. Successful implementation of this mitigation practice requires knowledge of the role of species identity and diversity on carbon accrual of plantations. Despite this need, solid data on the long‐term development of forest plantations are still very scarce. Monospecific and two species mixture plots of a 77‐year‐old tree diversity experiment in Yangambi in the Congo basin were fully inventoried. We calculated above‐ground C stocks using allometric equations, and soil C stocks by analyzing soil samples at multiple depths. Linear mixed effects models were used to analyze the effect of taxonomic and functional identity and diversity on the aboveground and soil carbon stocks. A high variability in aboveground C stocks across tree species combinations was observed. Apart from a species identity effect, the proportion of planted species in the total stand basal area (BApl ) and effective species richness were identified as compositional parameters with a significant effect on the aboveground carbon (AGC), with BApl being more important. Both AGC and BApl were coupled to the functional identity of the planted species; the planting of short‐lived pioneers led to low AGC. We found no clear benefits, but also no drawbacks, for AGC of two species mixture plots over monospecific plots or including nitrogen fixing species in the plantation scheme. However, the latter was the only compositional parameter with a significant positive effect on the soil carbon stock up to 1 m depth. We conclude that the different plantation configurations gave rise to a wide range in carbon stocks. This was predominantly caused by large differences in AGC sequestration over the past 77 years. Altogether, short‐lived pioneer species had a low BApl resulting in low carbon sequestration, while partial shade tolerant species achieved the highest AGC stocks. Tolerating spontaneous ingrowth during the plantation development can further increase the AGC stock, given that the appropriate functional type is planted.